Greece. (Studies in Growth with Equity.)
This report identifies emergency measures to address the most pressing needs of vulnerable groups, notably youth and jobless households. It also shows that a comprehensive strategy, involving action at the European level, would contribute to placing the Greek economy on a sustainable growth path.